2017
DOI: 10.1038/s41598-017-00993-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Astrocytic Support by Human Bone Marrow Stem Cell Grafts into Symptomatic ALS Mice towards Blood-Spinal Cord Barrier Repair

Abstract: Vascular pathology, including blood-CNS barrier (B-CNS-B) damage via endothelial cell (EC) degeneration, is a recently recognized hallmark of Amyotrophic Lateral Sclerosis (ALS) pathogenesis. B-CNS-B repair may be a new therapeutic approach for ALS. This study aimed to determine effects of transplanted unmodified human bone marrow CD34+ (hBM34+) cells into symptomatic G93A mice towards blood-spinal cord barrier (BSCB) repair. Thirteen weeks old G93A mice intravenously received one of three different doses of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 126 publications
12
73
1
Order By: Relevance
“…It is also notable that growing evidence suggests that endothelial cells are also affected in this disease, which in turn may cause progressive BBB alterations leading to infiltration of peripheral blood monocytes/macrophages. This has been confirmed in recent work by Garbuzova-Davis et al (2017 , 2019 ) as restoration of capillary integrity by delivery of human bone marrow stem cells reduced BBB permeability and delayed progression of disease in SOD1 mutant mice. Although the role and contribution of peripheral monocytes/macrophages in ALS-induced neurodegeneration remains elusive, these cells do have an important role in regulation of peripheral immunity.…”
Section: Cns Macrophage and Peripheral Immune Cell Contribution To Alsupporting
confidence: 52%
“…It is also notable that growing evidence suggests that endothelial cells are also affected in this disease, which in turn may cause progressive BBB alterations leading to infiltration of peripheral blood monocytes/macrophages. This has been confirmed in recent work by Garbuzova-Davis et al (2017 , 2019 ) as restoration of capillary integrity by delivery of human bone marrow stem cells reduced BBB permeability and delayed progression of disease in SOD1 mutant mice. Although the role and contribution of peripheral monocytes/macrophages in ALS-induced neurodegeneration remains elusive, these cells do have an important role in regulation of peripheral immunity.…”
Section: Cns Macrophage and Peripheral Immune Cell Contribution To Alsupporting
confidence: 52%
“…Since BSCB dysfunction is a potential contributor to ALS pathogenesis, restoration of BSCB integrity could be an important target in treatment development for ALS. We have recently shown that unmodified human bone marrow CD34 + (hBM34 + ) stem cells intravenously transplanted into symptomatic ALS mice dose-dependently differentiate into endothelial cells and engraft into the capillary walls in the cervical and lumbar spinal cords at 4 weeks post-transplantation [ 38 ]. Moreover, mice treated with the highest cell dose demonstrated improvements in behavioral disease outcomes and motor neuron survival in addition to reductions of macro- and microgliosis, maintenance of perivascular end-feet astrocytes, and reduction of capillary permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Novel treatment: developing new target and testing of multidrug therapy, stem cells grafting, growth factor therapy, antisense therapies, mitochondrial replacement therapy. [54][55][56][57][58] ( Dr. William Thomas Beaver is credited with drafting the initial regulations defining "adequate and controlled" clinical studies. Over the time, clinical trials have evolved into a standardized procedure, focusing on scientific assessment of efficacy and guarding the patient safety.…”
mentioning
confidence: 99%